Penerapan Tiga Motif Kain Tradisional pada Busana Wanita dengan Tema Transcultural pada Ajang Malang Fashion Week 2023 - Farika, Sephia; Nafiah, Annisau (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Indonesia has a variety of cultural heritage. One of the ancestral legacies is wastra, which is still preserved today. Wastra cloth is one of the works of art which is poured on traditional patterns. In this research, three different Indonesian fabric patterns used to a product in the form of women’s clothing. The cloth uses three wastra fabrics including Batik Parang, Jumputan, and Lurik. The aim of making this clothing is to find out how to combine three different fabric patterns to make it look harmonious. The method used in this research is the creation designs. There are three stages in clothing-making: determining the concept, drawing the design, and sewing the clothes. The clothing consists of four items: the blazer using Jumputan fabric and the trousers using two patterns, namely Batik Parang and Lurik.